Perilaku Rambat Retak di Daerah Lubang yang Terekspansi pada Aluminium Alloy - Syahrizal, Syahrizal; Purnowidodo, Anindito; Soenoko, Rudy (Jurnal Rekayasa Mesin, 2014)
Mechanism of crack propagation is done by loading the cycle against the perforated metal material will be difficult to avoid, to fatigue crack growth rate can be a way to expand its peg with the hole that normally uses metal balls as an alternative. By using a materials testing machine type cantilever bending eccentric crank, life time of the materials are determined. Research using the method of cold expansion hole in the aluminum alloy metal material to a hole with a diameter of 5 mm in expansion using pin with variation of ï¦ 5,1 mm, ï¦ 5,15 mm and ï¦ 5,2 mm made that crack found on the side of the hole would be difficult to propagate due to residual stress comparison. The result shows that there are residual stresses around the hole which varies depending on the diameter of the pin. In addition, there is growing tensile residual stress within a certain distance of the specimen being tested resulted in a faster growth rate, this causes the material usage time will be shorter.Keywords: cold expansion hole, materials testing machine, aluminumalloy, comparison residual stress, life time.